Determination of globotriaosylceramide analogs in the organs of a mouse model of Fabry disease - Ishii, Satoshi (J Biol Chem, 2020)
Fabry disease is a heritable lipid disorder caused by the low activity of α-galactosidase A and characterized by the systemic accumulation of globotriaosylceramide (Gb3). Recent studies have reported a structural heterogeneity of Gb3 in Fabry disease, including Gb3 isoforms with different fatty acids and Gb3 analogs with modifications on the sphingosine moiety. However, Gb3 assays are often performed only on the selected Gb3 isoforms. To precisely determine the total Gb3 concentration, here we established two methods for determining both Gb3 isoforms and analogs. One was the deacylation method, involving Gb3 treatment with sphingolipid ceramide N-deacylase, followed by an assay of the deacylated products, globotriaosylsphingosine (lyso-Gb3) and its analogs, by ultra-performance LC coupled to tandem MS (UPLC-MS/MS). The other method was a direct assay established in the present study for 37 Gb3 isoforms and analogs/isoforms by UPLC-MS/MS. Gb3s from the organs of symptomatic animals of a Fabry disease mouse model were mainly Gb3 isoforms and two Gb3 analogs, such as Gb3(+18) containing the lyso-Gb3(+18) moiety and Gb3(−2) containing the lyso-Gb3(−2) moiety. The total concentrations and Gb3 analog distributions determined by the two methods were comparable. Gb3(+18) levels were high in the kidneys (24% of total Gb3) and the liver (13%), and we observed Gb3(−2) in the heart (10%) and the kidneys (5%). These results indicate organ-specific expression of Gb3 analogs, insights that may lead to a deeper understanding of the pathophysiology of Fabry disease.